Children and television consumption in the digital era : use, impact and regulation - Gunter, Barrie (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Children and Television Consumption in the Digital Era provides a comprehensive analysis of contemporary research on the developmental impact of children's screen engagement in modern society. Barrie Gunter explores how the world of television has evolved to become almost unrecognisable from the broadcast landscapes present over the last years of the 20th century. This key text considers how screen-based entertainment has become increasingly interactive, and how children have become accustomed to creating their own television schedules through streamed services. It explores key topics including screen experiences and the manifestation of prosocial and antisocial behaviour, advertising and the development of consumerism, and the evidence of screen time on a child's health and school performance. Gunter insightfully assesses television content that children are exposed to and its impact on cognitive and behavioural development. Featuring commentary on the challenges regulators face to keep up with rapidly developing screen technologies and suggestions on how parents can mediate their children's screen behaviour, this text is an essential read for researchers and students taking courses in child development, family studies, broadcasting and communication.
OCLC-licensed vendor bibliographic record.
Keywords: Television and children; EDUCATION / Computers & Technology; FAMILY & RELATIONSHIPS / Activities; FAMILY & RELATIONSHIPS / Life Stages / Adolescence